2022
DOI: 10.54783/endlessjournal.v5i2.89
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multimedia-Based Education on the Management of Hypertension on Behavioral Change for Stroke Prevention

Abstract: This study aims to determine the effect of multimedia-based education on the management of hypertension on changes in stroke prevention behavior. The method in this study uses a quasi-experimental pre-post and post-test with control group design. The study population was all elderly with hypertension in Cipayung District, East Jakarta. The sampling technique uses purposive sampling. The number of samples in 64 respondents, in the intervention group and the control group. The method of data collection by pre-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
0
0
1
Order By: Relevance
“…Hal ini dikarenakan edukasi kesehatan sendiri ialah suatu proses yang ditujukan guna meningkatkan pengetahuan, sikap serta kebiasaan seorang individu yang berhubungan dengan kesehatan (Sebayang, 2022). Selain itu, edukasi kesehatan turut ditujukan untuk mengubah pengambilan keputusan terkait tindakan yang berkaitan dengan kesehatan (Suratun et al, 2022). Edukasi kesehatan ialah suatu cara yang disusun guna mempengaruhi orang lain baik dalam bentuk perorangan maupun kelompok (Muslihati et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…Hal ini dikarenakan edukasi kesehatan sendiri ialah suatu proses yang ditujukan guna meningkatkan pengetahuan, sikap serta kebiasaan seorang individu yang berhubungan dengan kesehatan (Sebayang, 2022). Selain itu, edukasi kesehatan turut ditujukan untuk mengubah pengambilan keputusan terkait tindakan yang berkaitan dengan kesehatan (Suratun et al, 2022). Edukasi kesehatan ialah suatu cara yang disusun guna mempengaruhi orang lain baik dalam bentuk perorangan maupun kelompok (Muslihati et al, 2018).…”
Section: Hasil Dan Pembahasanunclassified
“…Several studies have found that education can increase a person's knowledge and awareness of stroke symptoms, stroke emergencies, and stroke prevention management [11], [12]. In addition, education can improve a person's attitude in primary prevention [13].…”
Section: Introductionmentioning
confidence: 99%